PERAN UN WOMEN PADA PEMBERDAYAAN PEREMPUAN DI BIDANG POLITIK SURIAH PADA 2019-2023 - Wahyudi, Aldi Dwi Pusla; Retnaningsih, Umi Oktyari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Women can play important roles in shaping the world, including contributing to the struggle for peace in conflict-affected countries such as Syria. UN Women has been instrumental in empowering women and supporting their participation in peacebuilding. This article discusses in depth the role of this organization in helping Syrian women to create peace. To address this topic, a qualitative research method was employed, utilizing document analysis techniques with data sourced from the official UN Women website, along with books, international and national journals, and international news outlets. This research also adopts the perspective of Pluralism, using the theory of International Organizations as outlined by Clive Archer. The research highlights the role of UN Women in three key aspects: first, as an actor supporting the Syrian political process based on UN Security Council Resolutions 1325 and 2254, particularly in promoting women's participation in Syria. Second, as an arena, through the establishment of the Women's Advisory Board (WAB) and its role in advancing women's participation in conflict resolution, serving as one of UN Women's main instruments. .Keywords: UN Women, Empowerment, Women's Participation, Syrian Conflict, Conflict Resolution